2008
DOI: 10.1057/palgrave.jors.2602430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating trust in electronic commerce: a study based on the information provided on merchants’ websites

Abstract: Lack of trust has been identified as a major problem hampering the growth of Electronic Commerce (EC). It is reported by many studies that a large number of online shoppers abandon their transactions because they do not trust the website when they are asked to provide personal information. To support trust, we developed an information framework model based on research on EC trust. The model is based on the information a consumer expects to find on an EC website and that is shown from the literature to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
0
26
0
3
Order By: Relevance
“…Indeed, a sense of chaos in the ECommerce marketplace might be felt by customers; for example, they may fear that their personal information could be stolen due to untrustworthy online companies (Head, and Hassanein, 2002). It is well known that information accuracy, which is found in the E-Commerce websites, is incomplete (Meziane and Kasiran 2008). Some businesses claim to have a 'privacy policy', however there is no assurance that it can be found on the merchants' websites and the reviews that are found on many of these websites are hard to verify that they are from genuine consumers (Meziane and Kasiran 2008).…”
Section: Social and Third Party Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a sense of chaos in the ECommerce marketplace might be felt by customers; for example, they may fear that their personal information could be stolen due to untrustworthy online companies (Head, and Hassanein, 2002). It is well known that information accuracy, which is found in the E-Commerce websites, is incomplete (Meziane and Kasiran 2008). Some businesses claim to have a 'privacy policy', however there is no assurance that it can be found on the merchants' websites and the reviews that are found on many of these websites are hard to verify that they are from genuine consumers (Meziane and Kasiran 2008).…”
Section: Social and Third Party Recommendationsmentioning
confidence: 99%
“…It is well known that information accuracy, which is found in the E-Commerce websites, is incomplete (Meziane and Kasiran 2008). Some businesses claim to have a 'privacy policy', however there is no assurance that it can be found on the merchants' websites and the reviews that are found on many of these websites are hard to verify that they are from genuine consumers (Meziane and Kasiran 2008). Therefore, friends and family members' recommendations enhance the trust of some business websites (Nor and Pearson, 2008).…”
Section: Social and Third Party Recommendationsmentioning
confidence: 99%
“…However, this dramatically decreases in online markets. The absence of trust is identified as the main issue obstructing the development of EC [3,6]. Trust is always a strong factor in developing and maintaining relationships.…”
Section: Bmentioning
confidence: 99%
“…In Saudi Arabia the infrastructure of EC is not forthcoming because of the monopoly of Internet service providers [7] though Saudi customers would be encouraged to engage in EC if the facilities are provided [1]. Security and Integrity have been identified as the main concern in reference to trust relating to technology [3]. In another study, Internet payment systems have been identified as a major trust concern [7].…”
Section: Cmentioning
confidence: 99%
“…In e-commerce platforms, where wide range of business activities that accommodate online products and services available for customers and business owners (Aulkemeier et al, 2015;Meziane & Kasiran, 2008;Ranganathan & Ganapathy, 2002) can be executed, deployment on cloudbased environment is economical and technologically reliable, but highly prone to security issues, especially the Business to Consumer (B2C) ecommerce model (Thaw, Mahmood, & Dominic, 2009;Pavlou, 2003). The B2C characterises e-commerce activities like purchasing, selling and exchange of goods and services via a computer network in an electronic form (Digitsmith, 2011 Authenticating the true identities of the receivers of associated transaction documents in a B2C e-commerce platforms, in a cloud-based environment, is still experiencing unresolved issues, owing to the deficiencies of the prominently-used XML signatures (Ramgovind et al, 2010;Siani & Charlesworth, 2009).…”
Section: Introductionmentioning
confidence: 99%